Implementation of Social Care Attitude in Primary Schools - Dwi Nurhayati (International Journal of Students Education, 2024)
The implementation of sosial care attitudes in elementary schools is crucial in shaping the character and personality of students from an early age. This study aims to explore effective methods and strategies in teaching sosial care attitudes to elementary school students. Through a qualitative approach, data was collected through observation, interviews, and document analysis. The results of the study indicate that the implementation of sosial care attitudes can be achieved through collaborative learning, sosial projects, and direct experiences in the community. , namely research that presents data in the form of sentences obtained directly The data in this research was collected through questionnaires, The subjects in this research were all students at PAB 5 KLumpang Private Elementary School. The implications of this research highlight the active role of teachers and schools in guiding students to become individuals who care about their sosial environment. Further research could be conducted to identify factors that influence the effectiveness of implementing sosial care attitudes in elementary schools.